(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ginsenosides, the active components of ginseng, have been demonstrated to modulate a wide range of physiological functions, lending credence to the herb’s medicinal potential. Before illustrating how ginsenosides exercise their effects via interactions with steroidal receptors, this article will examine the structure, systemic transformation, and bioavailability of these compounds. Ginsenosides are valuable resources for the creation of new modalities due to their wide range of biological activities. But ginsenoside’s poor bioavailability is a major barrier that must be solved before it can be widely used in clinical practise